Effect of bovine Somatotropin (bST) on peripubertal growth rates of Holstein heifers fed two planes of nutrition - Garcia Gavidia, A.; Feitsma, D.; Hayen, M.J.; Cline, L.; Head, H.H.; Wilcox, C.J. (Revista Científica de la Facultad de Ciencias Veterinarias)
Three groups of Holstein heifers were utilized (N = I,39; II,63; III, 183) for growth rates of about 0.675 (control) or 0.900 (high) kg/d from 50 or 90 to 365 days of age. Heifers were fed either alfalfa silage or corn silage plus grain concentrate. Body weights and heights at withers were measured biweekly. Daily injections of 8.25, 12.36 mg of bST (I and II) from 220 to 340 days of age and 500 mg of bST/14 d (III); other heifers received injections of excipient or no injections. During both, the overall and bST injection periods body weight increase within the groups were greater for bST injected heifers than not injected for high or control diets. Total increases in height at withers for heifers on high diets were greater than in control fed heifers for groups I and II but not III. Before bST injections high fed heifers grew faster than control for all experiments. Total increases in height at withers during the bST injection period were greater for heifers on high diet for II but not for I and III. No improvement in height was detected for control heifers in any of the three experiments. Results indicated that injecting growing heifers with bST around the Peripubertal period increase body weight gain. Furthermore, no overall effect of bST was large nor persisted until the heifers were bred.